Estimation of volume, biomass, and carbon of coarse woody debris in native forests in São Paulo State, Brazil - Moreira, Andrea Bittencourt (2017)
The objective of this study was to test the line intersect sampling (LIS) methodology using the design-based inference with stratified systematic sampling and two transect shapes: a straight line and a cross shape, both with three different lengths (100, 150, and 200 m) to estimate the number of coarse woody debris (CWD) elements, their volume, biomass and carbon stocks; by decay class; furthermore, we fit and select CWD biomass and carbon models. The study area includes two types of native forest in the State of São Paulo, Brazil: a Seasonal Semi-deciduous Forest (SSF) and a Cerrado sensu-stricto (CSS). Two strata were chosen in each area, and in each stratum ten sampling units were installed according to a systematic sampling protocol. Each sampling unit had one North- South line of 200 m superimposed over the other lengths (100 and 150 m) and three lines (one for each length) in the East-West direction forming the cross shapes, for a total 650 m per sampling unit. All CWD elements with a diameter _ 10 cm that crossed the transect were tallied. For each element, the diameter, length, perpendicular width, decay class, and (when possible) species was recorded. Disc samples were taken from each element, from which cylinder samples were extracted then oven dried to determine density. These cylinders were milled and analyzed to determine carbon content (%). The volume of each element was calculated by taking the difference between cross-sectional area and any hollowed area, then multiplying by the element\'s length. Biomass was calculated by multiplying volume values by density values, and carbon stocks were calculated by multiplying biomass by the carbon percentage factors computed via lab analysis. Total estimators were calculated by area and per hectare for the number of CWD elements, their volume, biomass, and carbon stocks. These estimators were calculated by stratum then combined across the entire sample population. The data from each sampling unit was also used to calculate the wood density and carbon concentration by decay class, as well as to fit linear and nonlinear models. For the SSF area, the most accurate transect design was the 200 m cross shaped; and for the CSS area was selected the 150 m cross shape. Both areas showed lower biomass values (1.3 and 6.7 Mg/ha for the CSS and SSF areas, respectively) than other studies in the Amazon Forest where CWD research has been conducted. In both areas, as the decay class increased (from least to most rotten material), wood density decreased, which follows the same pattern as other literature. Carbon concentration barely changed within decay classes. Using a conversion constant of 50%, similar carbon stock results were obtained. Nonlinear models (using diameter and length as predictor variables) proved an efficient tool for predicting CWD biomass at an element level. As expected, biomass data exhibited heteroscedasticity, which was mitigated by modeling the variance of the residuals with a power function of the combined variable. Adding decay class as an indicator variable also resulted in model improvement.